Pemulihan Ekonomi Petani Lokal Petungkriyono melalui Optimalisasi Pemasaran Beras Hitam - Tjahja Muhandri; Anni Syafa’ah; Mufti Abdillah; Ita Vera; Dilla Ferawati; Akhmad Sofyan Khalim (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2021)
Genau Black Rice is a native Javanese black rice variety which is one of the superior products of Tlogopakis Village, Petungkriyono District, Pekalongan Regency, Central Java. Currently, this superior product is experiencing obstacles in its marketing. IPB Goes To Field (IGTF) Domicile 2020 from Semanka Team aims to introduce Genau Black Rice to the wider community and increase sales of Genau Black Rice at BUMDes Tlogopakis, which is a sales intermediary from farmers to customers. This paper uses a qualitative and quantitative approach by conducting a field study in the form of direct interviews with BUMDes and black rice farmers in Tlogopakis Village, as well as comparing sales data during the pandemic before the IGTF activity and after the activity. The success of IGTF activities in order to optimize the marketing of Genau Black Rice is the creation of new product designs from packaging redesign and rice sorting and grading, the emergence of new marketing methods with digital marketing, and increased profits and sales during the pandemic. Efforts for the sustainability of the program are being taken by registering BUMDes Tlogopakis at the Mitra Tani Market organized by the Pekalongan Regency Food and Agriculture Security Service (DKPP), marketing Genau Black Rice products to tours in Petungkriyono, submitting funds to BUMD of Pekalongan Regency in in order to improve the quality of Genau Black Rice production, and motivate the youth of Tlogopakis Village to take over the social media accounts for Genau Black Rice that have been formed through the IGTF program so that digital marketing can continue. Keywords: BUMDes Tlogopakis, digital marketing, genau black rice